Efisiensi Pengunaan Faktor-faktor produksi Pada Usahatani Brokoli Dikelurahan Kakaskasen Kecamatan Tomohon Utara Kota Tomohon - Christy P. Tuwongkesong; Juliana R. Mandey; Rine Kaunang; Ellen G. Tangkere (COCOS, 2013)
ABSTRACTThe objective of this research is to analyze the efficiency of production factor use of Broccoli farming. Aims to analyze the efficiency the use of production factors of in broccoli farming. This study was conducted in Kakaskasen for five months, starting from October until February, 2013. This study has been conducted on all existing broccoli farmers in Kakaskasen village. Datais analyzed by using descriptive analysis, to describe the characteristics of broccoli farmers and characteristics broccoli farm, and regression analysis with cobb-douglas production function to describe the relationship between the production of broccoli with the factors of production. Analyses were performed by using Minitab 16 program. Economic efficiency of each factors of production can be seen from the ratio of the value of the marginal product of an input X1with the input prices.The results showed that an average area of land cultivated by 0.41 Ha, the average utilization of 0.118 kg/ha, the average utilization of manure by 493.83 kg/ha, the average usage of 198.33 kg/ha NPK, average The average use of urea fertilizer was 207.08 kg/ha and the average utilization of 70.93 person-days of labor per ha. Technically efficient use of seed production factor, labor, manure and NPK fertilizer was efficient and the use of production factors land area is still not efficient, while the use of factors of production was not efficient. Economically, the use of factors of production land, labor seeds, manure and NPK fertilizer still yet efficient, while the use of factors of production and urea fertilizer not efficient.To increase the production of land can still be used. In addition, the use of urea fertilizer should be reduced because their use was excessive.